2014
DOI: 10.1002/chem.201402981
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Hydroformylation/Diels–Alder Processes: One‐Pot Synthesis of Polysubstituted Cyclohexenes, Cyclohexadienes, and Phthalates from Alkynes

Abstract: A novel, one-pot hydroformylation/Diels-Alder sequence for the synthesis of multisubstituted cyclohexenes, cyclohexadienes, and phthalates has been developed. Various alkynes were efficiently converted into the corresponding products in good yields and with excellent diastereoselectivity through palladium-catalyzed hydroformylation followed by an AAD-type reaction (AAD: Amides-Aldehydes-Dienophiles). In view of the availability of the substrates, the atom-efficiency of the overall process, and the convenient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…One year later, in order to demonstrate the additional utility of the hydroformylation method, Beller et al reported an expeditious protocol for the synthesis of the polysubstituted cyclohexene and cyclohexadiene derivatives by adopting their palladium-based method into a sequential hydroformylation/ condensation/Diels-Alder process. [79] Considering the requisite of PTSA in the entire process, the authors envisioned the overall transformation to be realized in a two-step-one-pot fashion. First, the internal alkynes were converted to corresponding α,βunsaturated aldehydes under syngas in the presence of the palladium-based catalyst.…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…One year later, in order to demonstrate the additional utility of the hydroformylation method, Beller et al reported an expeditious protocol for the synthesis of the polysubstituted cyclohexene and cyclohexadiene derivatives by adopting their palladium-based method into a sequential hydroformylation/ condensation/Diels-Alder process. [79] Considering the requisite of PTSA in the entire process, the authors envisioned the overall transformation to be realized in a two-step-one-pot fashion. First, the internal alkynes were converted to corresponding α,βunsaturated aldehydes under syngas in the presence of the palladium-based catalyst.…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…Therefore, many early protocols of hydroformylation of alkynes formed the target unsaturated aldehydes in low yields. During the past two decades, several methods of rhodium‐catalyzed hydroformylation of alkynes were reported, demonstrating that the selective production of α,β‐unsaturated aldehydes from alkynes is feasible [62–66,68,69,71,72,75–77,79] . Hereafter, only the palladium‐catalyzed hydroformylation of alkynes will be discussed.…”
Section: Pd‐catalyzed Hydroformylation Of Alkynesmentioning
confidence: 99%
“…Three‐component coupling reactions containing aldehydes, dienophiles, and orthoesters allow for a rapid entry to O ‐alkyl substituted cyclohexenes . The mechanism involves condensation of aldehydes with orthoesters to generate 1‐alkoxy‐1,3‐butadienes as key intermediates 156 , which subsequently are trapped by electron‐deficient dienophiles in a Diels‐ Alder reaction (Scheme , A ). Unlike anhydrides and acid chloride, TMOF and TEOF act as water detracting reagents as well as alcohol donors without the need to use molecular sieves and/ or Na 2 SO 4 .…”
Section: Carbon‐carbon and Carbon‐heteroatom Bond Formation Reactionsmentioning
confidence: 99%
“…This multicomponent reaction was developed for the preparation of hexahydroisoindole derivatives (Scheme , B ). Likewise, multisubstituted cyclohexene can be synthesized through condensation of TMOF with an alkyne and N ‐methylmaleimide as the dienophile (Scheme , C ).…”
Section: Carbon‐carbon and Carbon‐heteroatom Bond Formation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation